FLORESCIMENTO E FRUTIFICAÇÃO DA MANGUEIRA (Mangifera indica L.) VARIEDADE HADEN - Simão, Salim; Doni, Maria Elisabete; Barbin, Décio (REVISTA DE AGRICULTURA, 2015)
FLORESCIMENTO E FRUTIFICAÇÃO DA MANGUEIRA (Mangifera indica L.) VARIEDADE HADEN